Implikasi Kebijakan Pajak Digital Terhadap Aktivitas Ekonomi Generasi Z di Era Transformasi Digital Indonesia - Al-Lust, Amara Bahisa; Mas’ud, Diana Khaqiya; Wulansari, Malaynia Senja; Agustanta, Nainta (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2025)
This research examines the implications of digital tax policy on Generation Z's economic activities in Indonesia's digital transformation era. The study aims to analyze the impact of digital tax policies on consumption behavior and business ventures involving Generation Z, examine their responsiveness to these policies, identify challenges and opportunities in adapting to the increasingly regulated digital economy, and measure their contribution to state revenue through digital tax compliance. Using literature review and library research methodologies, this study analyzes how digital tax policies, including the implementation of 10% Value Added Tax (VAT) on digital products and services, influence Generation Z's consumption patterns and business strategies. The findings reveal that the implementation of this policy has resulted in significant changes in Generation Z's digital consumption behavior, where they tend to become more selective and prioritize spending on essential needs. As MSMEs operators, Generation Z faces challenges in adapting to this policy, particularly in adjusting profit margins and marketing strategies. Some MSMEs have responded by adopting product diversification strategies and digital marketing innovations, while others struggle to adapt due to limited access to technology and financial literacy. The research concludes that while digital tax policies present challenges for Generation Z's economic activities, they also promote increased tax literacy and innovation in business strategies. The study recommends the necessity of involving Generation Z in the policy-making process to ensure more effective and equitable implementation of digital tax policies.Keywords: digital tax, generation z, digital economy